Functional Optimization of Broadly Neutralizing HIV-1 Antibody 10E8 by Promotion of Membrane Interactions - Rujas, Edurne (J Virol, 2018)
The 10E8 antibody targets a helical epitope in the membrane-proximal external region (MPER) and transmembrane domain (TMD) of the envelope glycoprotein (Env) subunit gp41 and is among the broadest known neutralizing antibodies against HIV-1. Accordingly, this antibody and its mechanism of action valuably inform the design of effective vaccines and immunotherapies. 10E8 exhibits unusual adaptations to attain specific, high-affinity binding to the MPER at the viral membrane interface. Reversing the charge of the basic paratope surface (from net positive to net negative) reportedly lowered its neutralization potency. Here, we hypothesized that by increasing the net positive charge in similar polar surface patches, the neutralization potency of the antibody may be enhanced. We found that an increased positive charge at this paratope surface strengthened an electrostatic interaction between the antibody and lipid bilayers, enabling 10E8 to interact spontaneously with membranes. Notably, the modified 10E8 antibody did not gain any apparent polyreactivity and neutralized virus with a significantly greater potency. Binding analyses indicated that the optimized 10E8 antibody bound with a higher affinity to the epitope peptide anchored in lipid bilayers and to Env spikes on virions. Overall, our data provide a proof of principle for the rational optimization of 10E8 via manipulation of its interaction with the membrane element of its epitope. However, the observation that a similar mutation strategy did not affect the potency of the first-generation anti-MPER antibody 4E10 shows possible limitations of this principle. Altogether, our results emphasize the crucial role played by the viral membrane in the antigenicity of the MPER-TMD of HIV-1. IMPORTANCE The broadly neutralizing antibody 10E8 blocks infection by nearly all HIV-1 isolates, a capacity which vaccine design seeks to reproduce. Engineered versions of this antibody also represent a promising treatment for HIV infection by passive immunization. Understanding its mechanism of action is therefore important to help in developing effective vaccines and biologics to combat HIV/AIDS. 10E8 engages its helical MPER epitope where the base of the envelope spike submerges into the viral membrane. To enable this interaction, this antibody evolved an unusual property: the ability to interact with the membrane surface. Here, we provide evidence that 10E8 can be made more effective by enhancing its interactions with membranes. Our findings strengthen the idea that to elicit antibodies similar to 10E8, vaccines must reproduce the membrane environment where these antibodies perform their function.